2012
DOI: 10.1007/s00339-012-6916-4
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of CaGa2O4, Ca2GeO4, CaIn2O4 and CaSnO3 prepared by electrospinning

Abstract: CaGa 2 O 4 nanofibers, Ca 2 GeO 4 microfibers, CaIn 2 O 4 nanorods, and CaSnO 3 nanofibers were synthesized by using an electrospinning technique. Structures and morphologies of the as-synthesized oxides were characterized by X-ray diffraction and scanning electron microscopy, respectively. Raman and infrared spectra were also recorded and analyzed at room temperature. More significantly, nuclear site group analysis was carried out and the number of normal vibrational modes, Raman-active, and infraredactive op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The bands located at 161, 181, 276 and 354 cm -1 were assigned to Ca-SnO 3 and O-Sn-O vibrations [30]. The bands at 441, 583 and 701 cm -1 were related to the torsional and stretching modes of SnO 3 and Sn-O, respectively [30,32,35]. The modes at 1079 and 1092 cm -1 were assigned to calcium carbonate vibrations [36].…”
Section: Characterization Of the Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bands located at 161, 181, 276 and 354 cm -1 were assigned to Ca-SnO 3 and O-Sn-O vibrations [30]. The bands at 441, 583 and 701 cm -1 were related to the torsional and stretching modes of SnO 3 and Sn-O, respectively [30,32,35]. The modes at 1079 and 1092 cm -1 were assigned to calcium carbonate vibrations [36].…”
Section: Characterization Of the Materialsmentioning
confidence: 99%
“…The bands located at 870, 1051, and 1454 cm -1 were assigned to carbonate vibrations [31], and the band at 1643 cm -1 was associated with water angular deformation. The vibrations assigned to stannates (SnO 3 2-) generally produce highintensity bands in the infrared region at 300-400 cm -1 and 600-700 cm -1 with a band broadening typical of orthorhombic perovskite structures [27,32]. The mid-IR spectrum of CaSnO 3 showed a band at 641 cm -1 assigned to the stretching mode of Sn-O [33,34].…”
Section: Characterization Of the Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the IR part, a recent study by Zheng et al 33 reported an IR transmittance spectrum of CaSnO 3 in the range of 400-2000 cm −1 . As anticipated, only five peaks were reported (whose position in the spectrum is represented by vertical dashed lines in the upper panel of Figure 4) and tentatively assigned to stretching modes of Sn-O bonds and librations of the SnO 6 octahedra.…”
Section: B Spectroscopic Propertiesmentioning
confidence: 99%
“…In this respect, a large variety of infrared (IR) and Raman scattering measurements have been reported. 7,14,23,[25][26][27][28][29][30][31][32][33] Some of them measured Raman spectra at high temperatures 31 or pressures. 23 A recent theoretical study discussed the ambient pressure Raman spectrum just in terms of wave-numbers (intensities were not computed and, then, the full spectrum was not reproduced).…”
Section: Introductionmentioning
confidence: 99%